Islamic Fintech as an Alternative to Increase Access to Capital for MSMEs: A Bibliometric Review - Hadyantari, Faizatu Almas; Surbakti, Mhd Handika (JURNAL EKONOMI SYARIAH, 2024)
Introduction to The Problem: It is known that MSMEs contribute 60.3 per cent to GDP and can absorb 97 per cent of the workforce in Indonesia, but there are still challenges, one of which is access to capital from financial institutionsPurpose/Objective Study: This study explores the potential and role of Islamic fintech in improving access to finance for Micro, Small and Medium Enterprises (MSMEs) through bibliometric analyzis.Design/Methodology/Approach:This research utilizes bibliometric analysis and keyword searches of “Islam”, “Fintech”, and “SMEs” to develop research results and provide implementation recommendations.Findings: Based on the keywords “Islamic”, “Fintech”, and “SME” obtained through indexed publication literature, the keywords “fintech”, “investment”, and “Islamic-compliant financing” are keywords that have the potential to be studied more deeply. The author recommends the utilisation of Islamic fintech as an alternative access to capital through Islamic Peer-to-peer lending (P2P) and Islamic Security Crowdfunding Finance schemes.Paper Type: Research Article